2006
DOI: 10.1002/mrm.20859
|View full text |Cite
|
Sign up to set email alerts
|

Subsecond fluorine‐19 MRI of the lung

Abstract: Minimal scan times in rapid fluorine-19 MRI using sulfur hexafluoride (SF 6 ) have been on the order of 10 s. Because of the very short T 1 relaxation time of SF 6 (T 1 ‫؍‬ 1.65 ms), high receiver bandwidths are necessary to allow for a high number of excitations. Since high bandwidths cause high levels of electronic noise, SNR per acquisition has been too low to further reduce scan time. The purpose of this study was to investigate whether scan times could be reduced using hexafluoroethane (C 2 F 6 ), a gas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…38,39 As this is a descriptive report of initial experiences, an increase in baseline intensities from their background noise levels defi nes properly ventilated areas, whereas ventilation defects were defi ned by the lack of signal due to minimal or no infl ow of the gaseous contrast agents to the lung FOV. Subjects were provided with adequate information pertaining to the details of the acquisitions and what was expected from them (eg, breath-holds, respiratory efforts), resulting in minimal subject coaching throughout the imaging sessions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 As this is a descriptive report of initial experiences, an increase in baseline intensities from their background noise levels defi nes properly ventilated areas, whereas ventilation defects were defi ned by the lack of signal due to minimal or no infl ow of the gaseous contrast agents to the lung FOV. Subjects were provided with adequate information pertaining to the details of the acquisitions and what was expected from them (eg, breath-holds, respiratory efforts), resulting in minimal subject coaching throughout the imaging sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Advances in the fi eld led to a number of studies in animal models (eg, swine, canine, rodents) [36][37][38][39] and excised human lungs, 40,41 demonstrating the suitabil ity of 19 F-enhanced MRI in regional assessments of pulmonary function. The renewable signal characteristics of PFP provide the means for assessing ventilationdefect severity, volume, and gas-trapping severity in patients with COPD and those with asthma, thus, providing a regional insight into the degree of underlying disease heterogeneity.…”
Section: Chestmentioning
confidence: 99%
“…Several studies have already demonstrated the interest of perfluorocarbons nanoemulsions for 19 F MRI. [15][16][17][18] In emulsions however, fluorinated molecules are easily accessible to other substances present in vivo such as oxygen [19] and since 19 F is exquisitely sensitive to perturbations in its microenvironment, chemical shifts may occur. [20] It is clear from the literature that both ultrasound and MRI contrast agents possess certain common requirements and that the development of polymeric capsules of perfluoroctyl bromide could provide dual imaging with these techniques.…”
mentioning
confidence: 99%
“…76Y79 Figure 3 shows lung images of a pig breathing 30% C 2 F 6 gas. 77 In clinical research, successful results were presented with the SF 6 gas. 80 Fluorinated gases have very short relaxation times (eg, T1 of 1.65 milliseconds for SF 6 and 7.9 milliseconds for C 2 F 6 ).…”
Section: Lung Ventilation Imagingmentioning
confidence: 94%
“…Image A was obtained in 260 milliseconds with an SNR of 7.9; image B, in 26 seconds with an SNR of 63. C, Postmortem 3D acquisition with a 6.3 Â 3.1 Â 8.0 mm 3 voxel size obtained in 10 minutes (adapted from Wolf et al77 ).…”
mentioning
confidence: 99%